Worldwide innovation: panel data analysis on the impact of the GEM's business environmental factors - Savosh, Kateryna (2020)
Innovation policy is a significant component of sustainable development. The successful increase in innovation needs to study what are the business environment factors that determine innovation activity. Such a goal will be reached using the panel data methods applied to data provided by the Global Entrepreneurship Monitor (GEM). This study concludes that worldwide factors as financing, government support, lower taxes and bureaucracy, entrepreneurship education in primary and secondary levels and the country’s economy openness present an important positive impact on innovation. The results are different if the analysis is made by level of income. None of the factors showed statistical evidence for low-income countries. Financing, basic school training and education, R&D transfer, and cultural and social norms have a positive impact on innovation in lower-middle-income countries. Financing, governmental support, reduced taxes and bureaucracy, and basic school training and education influence innovation activity in upper-middle-income economies. In high-income economies, present similar results.